Tori Spring’s Depression in Alice Oseman’s Solitaire - Arianingrum, Wakhida; Litaay, Adeline Grace M. (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study aims to analyse the symptoms, causes, and effects of depression experienced by the main character, Tori Spring, in Solitaire, a novel written by Alice Oseman. The research uses a descriptive qualitative method and applies Aaron T. Beck’s Cognitive Theory of Depression as the theoretical framework. The findings reveal that Tori shows several symptoms of depression, including insomnia, anhedonia, low self-esteem, self-blame, suicidal ideation, and appetite loss. These causes are triggered by various internal and external factors, such as repeated failures, lack of emotional support, family conflict, social rejection, and excessive guilt. The effects of Tori’s depression significantly impact her behaviour, thought patterns, and relationships with others. This study concludes that Solitaire presents a realistic portrayal of adolescent depression and emphasizes the importance of emotional understanding and mental health awareness. The analysis also highlights how literature can reflect complex psychological experiences, making it a valuable medium for exploring mental health issues. Keywords: Causes of depression, Effects of depression, Symptoms of depression